2010
DOI: 10.1111/j.1872-034x.2010.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined pre‐S deletion and core promoter mutations related to hepatocellular carcinoma: A nested case‐control study in China

Abstract: AFP levels >20 ng/mL, high HBV DNA levels, pre-S deletion, and T1762/A1764 double mutations at recruitment were independent risk factors of HCC. Combination of pre-S deletion and core promoter mutations increased the risk of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
(74 reference statements)
0
28
1
1
Order By: Relevance
“…and restrospective cohort studies show that pre-S deletion associates with hepatocarcinogenesis [Gao et al, 2007;Lin et al, 2007;Cao et al, 2008;Chen et al, 2008;Fang et al, 2008;Abe et al, 2009;Liu et al, 2009;Qu et al, 2011], only a few studies have dealt with the association between pre-S mutations and postoperative HCC recurrence. One of these was by Yeh et al [2010] who reported that short fragment (<100 bp) pre-S deletion in non-tumorus liver tissue correlated with a decreased disease-free survival, and that a pre-S stop codon mutation was associated with better disease-free survival after resection of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and restrospective cohort studies show that pre-S deletion associates with hepatocarcinogenesis [Gao et al, 2007;Lin et al, 2007;Cao et al, 2008;Chen et al, 2008;Fang et al, 2008;Abe et al, 2009;Liu et al, 2009;Qu et al, 2011], only a few studies have dealt with the association between pre-S mutations and postoperative HCC recurrence. One of these was by Yeh et al [2010] who reported that short fragment (<100 bp) pre-S deletion in non-tumorus liver tissue correlated with a decreased disease-free survival, and that a pre-S stop codon mutation was associated with better disease-free survival after resection of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-S mutant LHBs can upregulate cyclooxygenase-2 and cyclin A, thereby inducing hepatocyte cell cycle progression and proliferation [Wang et al, 2005]. Several cross-sectional and case-control studies show that some mutations in the HBV pre-S region associate significantly with an increased risk of developing HCC [Gao et al, 2007;Lin et al, 2007;Cao et al, 2008;Chen et al, 2008;Fang et al, 2008;Abe et al, 2009;Qu et al, 2011].…”
Section: Introductionmentioning
confidence: 98%
“…During the course of chronic HBV infection, a wide variety of liver diseases are observed, ranging from an asymptomatic carrier state to liver cirrhosis and HCC [16]. In our previous studies conducted in Qidong, pre- S deletion and specific mutations in BCP were confirmed to be associated with a high risk of HCC occurrence [17,18]. However, the risk of mutations in other regions of the full HBV genome was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…Base on the inclusion criteria, only 17 case-control studies (Sakamoto et al, 2006;Tanaka et al, 2006;Shinkai et al, 2007;Wang et al, 2007;Yuan et al, 2007;Zhang et al, 2007;Fang et al, 2008;Guo et al, 2008;Jang et al, 2008;Choi et al, 2009;Ja et al, 2009;Tangkijvanich et al, 2010;Welschinger et al, 2010;Zhu et al, 2010;Cho et al, 2011;Qu et al, 2011;Tatsukawa et al, 2011) with full-text were included in this meta-analysis and 18 studies were excluded. The flow chart of study selection is summarized in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%